2018
DOI: 10.4168/aair.2018.10.6.648
|View full text |Cite|
|
Sign up to set email alerts
|

Pollen-Food Allergy Syndrome in Korean Pollinosis Patients: A Nationwide Survey

Abstract: PurposePollen-food allergy syndrome (PFAS) is an immunoglobulin E (IgE)-mediated allergy in pollinosis patients caused by raw fruits and vegetables and is the most common food allergy in adults. However, there has been no nationwide study on PFAS in Korea. In this study, we investigated the prevalence and clinical characteristics of PFAS in Korea.MethodsTwenty-two investigators participated in this study, in which patients with allergic rhinoconjunctivitis and/or bronchial asthma with pollen allergy were enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 23 publications
4
54
1
Order By: Relevance
“…14) In a recent nationallevel multicenter study in South Korea, the prevalence of PFAS was 42.7% in pediatric patients with pollen allergy. 11) A recent the doctors estimated a much lower prevalence than what was actually published. The authors argued that it reflects a low index of suspicion and underdiagnosis of PFAS.…”
Section: Epidemiologymentioning
confidence: 93%
See 1 more Smart Citation
“…14) In a recent nationallevel multicenter study in South Korea, the prevalence of PFAS was 42.7% in pediatric patients with pollen allergy. 11) A recent the doctors estimated a much lower prevalence than what was actually published. The authors argued that it reflects a low index of suspicion and underdiagnosis of PFAS.…”
Section: Epidemiologymentioning
confidence: 93%
“…10) A recent Korean multicenter study reported that the prevalence of PFAS was 41.7% in patients with pollen allergy, 20%-30% in cases of sensitization to summer or autumn pollen alone, and higher than 50% in simultaneous sensitization to spring and autumn pollen or sensitization to all spring, summer, and autumn pollens. 11) Data on the prevalence of PFAS in children are limited. The prevalence of PFAS has been reported differently depending on the country, target group, and reporter.…”
Section: Epidemiologymentioning
confidence: 99%
“…Reactions of class 2 (≥ 0.70 IU/mL) or higher were considered positive 1819. Singleplex allergen-sIgE levels were measured using ImmunoCAP (Thermo Fisher Scientific/Phadia, Uppsala, Sweden); levels >0.35 kU/L were regarded as positive 1320. All tests were carried out according to the standard instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, several studies revealed the epidemiology of adult FA in Korea 11121314. However, as the study sample was relatively small, their findings may not represent nationwide trends; moreover, patients differed by institution and region.…”
Section: Introductionmentioning
confidence: 93%
“…In Europe, 70% of birch pollen allergy patients have accompanying varying degrees of food allergy [ 1 ]. Their symptoms are mainly shown after ingesting birch pollen-related foods [ 2 ], at least in part because of the cross-reaction between Bet v 1 homologous protein in food and the major allergen Bet v 1 in birch pollen, including apple (Mal d 1), cherry (Pru av. 1), pear (Pyr c 1), hazelnut (Cor a 1), celery (Api g 1), carrot (Dau c 1), soybean (Gly m 4), peanut (Ara h 8), jackfruit, and kiwi (Act d 8) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%